Insulin Protects Cardiac Myocytes from Doxorubicin Toxicity by Sp1-Mediated Transactivation of Survivin - Lee, Beom Seob (PLoS One, 2015)
Insulin inhibits ischemia/reperfusion-induced myocardial apoptosis through the PI3K/Akt/mTOR pathway. Survivin is a key regulator of anti-apoptosis against doxorubicin-induced cardiotoxicity. Insulin increases survivin expression in cardiac myocytes to mediate cytoprotection. However, the mechanism by which survivin mediates the protective effect of insulin against doxorubicin-associated injury remains to be determined. In this study, we demonstrated that pretreatment of H9c2 cardiac myocytes with insulin resulted in a significant decrease in doxorubicin-induced apoptotic cell death by reducing cytochrome c release and caspase-3 activation. Doxorubicin-induced reduction of survivin mRNA and protein levels was also significantly perturbed by insulin pretreatment. Reducing survivin expression with survivin siRNA abrogated insulin-mediated inhibition of caspase-3 activation, suggesting that insulin signals to survivin inhibited caspase-3 activation. Interestingly, pretreatment of H9c2 cells with insulin or MG132, a proteasome inhibitor, inhibited doxorubicin-induced degradation of the transcription factor Sp1. ChIP assay showed that pretreatment with insulin inhibited doxorubicin-stimulated Sp1 dissociation from the survivin promoter. Finally using pharmacological inhibitors of the PI3K pathway, we showed that insulin-mediated activation of the PI3K/Akt/mTORC1 pathway prevented doxorubicin-induced proteasome-mediated degradation of Sp1. Taken together, insulin pretreatment confers a protective effect against doxorubicin-induced cardiotoxicity by promoting Sp1-mediated transactivation of survivin to inhibit apoptosis. Our study is the first to define a role for survivin in cellular protection by insulin against doxorubicin-associated injury and show that Sp1 is a critical factor in the transcriptional regulation of survivin.